Assessing the Aftermath of COVID-19 Outbreak in the Agro-Food System: An Exploratory Study of Experts' Perspectives - Raptou, Elena; Mattas, Konstadinos; Tsakiridou, Efthimia; Baourakis, George (Frontiers in Nutrition, 2022)
The present study explored COVID-19 outbreak impacts on the food system in terms of agro-food production, distribution networks efficiency and emerging food consumption patterns according to food experts’ perspectives. Individual level data were selected from a sample of 59 executive managers of different domains representing agro-food businesses, agro-food cooperatives and agro-food consulting firms and public institutions. The empirical analysis addressed the effects of the COVID-19 crisis to all the stages in the food chain and attempted to indicate the factors that could influence the trajectory from “farm to fork” under uncertain circumstances. Factor analysis elicited the underlying dimensions of experts’ viewpoints toward the operation of the food system during COVID-19 pandemic. Data were also elaborated through hierarchical and k-means cluster analysis and the cluster structure was further validated by discriminant analysis. A two-cluster solution emerged, revealing differences in experts’ perceptions toward the aftermath of the pandemic on agriculture (socioeconomic impacts in rural areas, impacts in agricultural production), food processing businesses (decline in the economic viability of food businesses, sharp economic downturn in the food industry, economic recession, incentives for innovation), food distribution networks (distribution channels fallout, food supply disruption) and consumers’ food habits and preferences (increasing interest in health protection, adoption of unhealthy eating habits, demand for innovative and sustainable foods). These segments were identified as “skeptical food experts about COVID-19 impacts” (33.9%) and “alarmed food experts about COVID-19 impacts” (66.1%). Our findings highlighted the main disruptions that the food sector should overcome to meet consumer demand for safe and healthy food products and also ensure food availability and food system resiliency.